An 8-Month-Old Girl With Vesicular Rash. (March 2019) - Ozcan, Ali; Kahale, Kristin; Nguyen, Dan
This is a case report of an 8-month-old girl who presented to the pediatric emergency department with vesicular rash and fever. She was diagnosed with eczema herpeticum (EH). EH is an acute, rapidly progressive rare dermatologic disease, and if it is not treated promptly, it can cause life-threatening complications. It often occurs in a patient with an underlying skin disorder, such as atopic dermatitis or other erosive dermatoses. Diagnosis is mainly made by clinical examination usually presented as many very similar shaped and sized eroded vesicles. It is important for clinicians to recognize the sign and symptoms of EH and have a high suspicion for patients with atopic dermatitis who present with rapidly disseminating blisters. Treatment is with oral or intravenous acyclovir. If the patient has widespread eruptions or systemic symptoms such as fever, malaise, and poor oral intake, the patient should be admitted for intravenous acyclovir.